Unit-of-Use Versus Traditional Bulk Packaging - Tiffany So; Albert Wertheimer (University of Minnesota Libraries Publishing, 2012)
Background: The choice between unit-of-use versus traditional bulk packaging in the US has long been a continuous debate for drug manufacturers and pharmacies in order to have the most efficient and safest practices. Understanding the benefits of using unit-of-use packaging over bulk packaging by US drug manufacturers in terms of workflow efficiency, economical costs and medication safety in the pharmacy is sometimes challenging. Methods: A time-saving study comparing the time saved using unit-of-use packaging versus bulk packaging, was examined. Prices between unit-of-use versus bulk packages were compared by using the Red Book: Pharmacy's Fundamental Reference. Other articles were reviewed on the topics of counterfeiting, safe labeling, and implementation of unit-of-use packaging. Lastly, a cost-saving study was reviewed showing how medication adherence, due to improved packaging, could be cost-effective for patients. Results: When examining time, costs, medication adherence, and counterfeiting arguments, unit-of-use packaging proved to be beneficial for patients in all these terms.   Type: Student Project